INTERPRETATION OF THE CONCEPTS OF "CONCEPT" AND "CONCEPTOSPHERE" IN LINGUISTICS. (Scientific journal of the Fergana State University, 2025)
The article discusses how human beings understand the world through their worldview and mentality, and how this understanding is reflected in our language, within the fields of cognitive linguistics and linguoculturology. The article defines the history and development stages of cognitive linguistics. It deeply analyzes the connection between language and thought. Furthermore, it attempts to differentiate between concepts and notions that are the foundation of cognitive linguistics, and provides a detailed explanation of the concept of "conceptuosphere." Information about scholars and researchers who contributed to the development of cognitive linguistics is also provided.